Feminine Identity and Resistance in Azar Nafisi’s Reading Lolita in Tehran - Samra Charif (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
The present study examines feminine identity and resistance in Reading Lolita in Tehran, a memoir in books by Azar Nafisi. This personal memoir aims to capture the status of Iranian women, which has generated significant interest and numerous debates in political and literary circles, particularly after two unforgettable events in world history. This study investigates the formation of feminine identity by the author and her students, a recurring theme evident in many literary works, whether authored by Americans or Iranians. The search for female identity has been a common concern for Iranian women and their Iranian-American counterparts in various parts of the world. Iranian women have experienced marginalization and oppression, whether in their homeland or elsewhere. Therefore, the primary focus of this study is on the feminist perspective, conducted within the framework of Lila Ahmed and Lila Abu-Lughod, to capture the identity of Iranian women and to further the literary investigation canon to examine how Iranian resist the totalitarian regime to reclaim their identity and voice and seek refuge in literature. The findings of this study reveals the importance of literature in shaping feminine identity. For Nafisi and her students, literature is the peaceful sword through which they voice their struggles to the world
Keywords: Feminine Identity; Resistance; Agency; the Veil; the Islamic Republic of Iran